PENINGKATAN KEMAMPUAN KONEKSI MASALAH MATEMATIKA SISWA KELAS X SMA NEGERI 1 AIR JOMAN - Dewi Astuti (JURNAL MATHEMATIC PAEDAGOGIC, 2019)
Abstract This research was conducted based on the fact that there was a lack in student’s mathematical connection ability. The aim of this research was to examine the enhancement of student’s mathematical connection ability by Alberta model inquiry learning. This research used nonequivalent control group design. Population of this research was all engineering faculty UNA, and the samples were two classes selected by using purposive sampling technique, in which they were used as an experimental class and control class. The experimental class was treated by Alberta Model inquiry learning and control class by conventional learning. Instruments used in this research were mathematics connection ability test and observation sheet. Results showed that student’s mathematical connection ability enhancement in students received Alberta model inquiry learning was better than students who received conventional learning. Keywords: Inquiry Learning of Alberta Model, Mathematical Connection Ability